An Economic Analysis of Marketable Surplus of Paddy in Kathmandu District - Rajbanshi, Narayan Bhakta (1983)
The primary objective of the study is to identify factors determining the marketable suprlus of paddy for farmers in Kathmandu district. In addition, the study also examines the pattern of disposal of paddy among different categories of farmers. Cross-sectional data gathered through personal interviews of 119 farmers were utilized in the analysis. A multiple linear regression model was used to ascertain the factors influencing the marketable surplus. The variables hypothesized to have a significant effect on the dependent variables comprised paddy production, average price, family size per adult unit, and income from off-farm, and other sources. Elasticities were computed to show the response of the independent variables to changes in the dependent variable. Lorenz Curve and Gini ratio were employed to determine the pattern and degree of inequality of the distribution of marketable surplus among the four size groups of farmers in the district. Regression equation was estimated for the aggregate data as well as for each of two category levels. The category levels were based on the level of paddy production, those producing less than 60 muris fall into the first category, and those producing equal to or more than 60 muris into the second category. The regression analysis indicated that paddy production and family size per adult unit were two significant variables in determining the quantity marketed. Elasticity coefficients also showed that paddy production had a positive impact on the marketable surplus while family size had expected association with the dependent variable but with small coefficient. On the other hand, average price and income variables had no effect on the amount marketed, nor had they expected relationship with the dependent variable. The marketable surplus of paddy was unequally distributed among the farmers in the district. The analysis of Lorenz Curve and Gini ratio suggested that the larger the size of land holdings the more the quantity marketed. From results of the analysis certain measures to boost the marketable surplus by increasing the level of production were recommended. These include increasing the effectiveness of extension services, using more land saving techniques of production, increasing the availability of credit and seeds of high yielding varieties. Population curbing measures could also help reduce the level of consumption by the farmers, thereby increasing the quantity marketed.